Diabetes Dietary Scheduling Using Mobile App - Ahmad, Jasni; Teng Lim, Hui; Mong, Erene (International Journal of Engineering and Technology, 2018)
This paper introduces Diabetes Dietary Scheduling (DDS) mobile application which allows users who suffer from diabetes can follow the recipe provided and eat healthy. The facts show that there are many diabetics due to imbalance eating habits. DDS provides the recipes to the user so that user can eat health and get the nutrition of the foods user eat. DDS also provides recipe according to the diabetesâ€™ symptoms. Survey is the method used in DDSâ€™s formative evaluation. There are five experts involved in the survey. In the survey, DDS is tested in three dimensions which are usability, ease of use and user interface satisfaction.Â DDS is visually appealing but need to improve to be more users friendly. Â Â